BUDAYA ORGANISASI DAN KOMITMEN ORGANISASI PT. PERKEBUNAN NUSANTARA - Andi Nila Hardianti Alam; Muhammad Jufri; Asmulyani Asri (Jurnal Psikologi TALENTA, 2018)
Employee who has a big commitment to the company will increase the productivity and goal achievement of the company itself. This research is aimed to know the influence of organizational culture toward affective commitment, continuity commitment, and normative commitment in PT. Perkebunan Nusantara XIV. The subject of this research are 84 employees that chosen by Cluster Sampling Technique. This research used Simple Regressive Linear Test. The research result showed that there was positive influence of organizational culture toward affective commitment (p=0,000, Rsquare=0,269), there was no negative influence of organizational culture toward continuity commitment (p=0,000, Rsquare=0,168), and there was any positive influence of organizational culture toward normative commitment (p=0,000, Rsquare=0241). This research may have a benefit for the company making the employee owns the responsibility to implement the important aspects of organizational culture